2022
DOI: 10.1111/rec.13625
|View full text |Cite
|
Sign up to set email alerts
|

Performance of innovative materials as recruitment substrates for coral restoration

Abstract: Artificial reefs and, more recently, ecoengineering are frequently advocated as possible tools to counteract the loss of tropical coral reefs worldwide. Despite increasing availability of novel materials, there is limited understanding of how different materials and their physical and chemical properties can influence coral recruitment success and early benthic community development. This study investigated the efficacy of several innovative materials as recruitment substrates for corals and other sessile bent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 83 publications
(122 reference statements)
0
15
0
Order By: Relevance
“…1B), including acrylic, polyvinyl chloride plastic, unglazed terracotta, custom‐moulded cement or clay, tyres, and dead coral colonies cut into slabs (e.g. Fitzhardinge & Bailey‐Brock, 1989; Price, 2010; Harriott & Fisk, 1987; Doropoulos et al ., 2016; Leonard et al ., 2022), and it is well known that the type of material influences the corals that recruit to their surfaces (Harriott & Fisk, 1987; Leonard et al ., 2022).…”
Section: Methodologies For Quantifying Recruitsmentioning
confidence: 99%
“…1B), including acrylic, polyvinyl chloride plastic, unglazed terracotta, custom‐moulded cement or clay, tyres, and dead coral colonies cut into slabs (e.g. Fitzhardinge & Bailey‐Brock, 1989; Price, 2010; Harriott & Fisk, 1987; Doropoulos et al ., 2016; Leonard et al ., 2022), and it is well known that the type of material influences the corals that recruit to their surfaces (Harriott & Fisk, 1987; Leonard et al ., 2022).…”
Section: Methodologies For Quantifying Recruitsmentioning
confidence: 99%
“…The ARs' configuration is the key factor in influencing the attraction effect. Studies have shown that artificial materials' microstructure complexity and durability can strongly influence attraction [3]. More complex structures attracted more species [45,46].…”
Section: Influence Of Ars' Configurationmentioning
confidence: 99%
“…Marine fisheries are a critical global food supply element and are significant for many countries and regions [1]; however, many marine species, habitats, and ecosystems have suffered catastrophic declines [2][3][4] due to increased pollution, the development and hardening of coastlines, the extraction of resources, and the introduction of invasive species [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Proxies of recruitment have commonly been quantified using recruitment tiles made of diverse materials and shapes (e.g. Harriott & Fisk, 1987;Herbert & Hawkins, 2006;Leonard et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Proxies of recruitment have commonly been quantified using recruitment tiles made of diverse materials and shapes (e.g. Harriott & Fisk, 1987; Herbert & Hawkins, 2006; Leonard et al, 2022). However, the use of artificial substrata to quantify recruitment introduces some level of bias related to: tile materials, tile orientation, duration of conditioning timeframe (and associated fouling communities), handling, change of environmental conditions during laboratory work and/or following bleaching and drying treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%